2019
DOI: 10.1016/j.ajoc.2019.100478
|View full text |Cite
|
Sign up to set email alerts
|

Bilateral pulmonary emboli following macular hole surgery with postoperative prone positioning

Abstract: Purpose To report a rare case of bilateral pulmonary emboli following pars plana vitrectomy with postoperative prone positioning. Observations A 60 year-old female presented with a fourmonth history of unilateral distorted vision. Ocular coherence tomography revealed a full thickness macular hole. Two weeks later, the patient underwent a 23-gauge pars plana vitrectomy with internal limiting membrane peeling and 12% perfluoropropane gas tamponade. Postoperatively, she co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…The contemporary literature consists of a case series [3], from Turkey and 2 case reports [4,5]. The case series from Turkey reported 6 cases of PE following ophthalmic surgeries.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The contemporary literature consists of a case series [3], from Turkey and 2 case reports [4,5]. The case series from Turkey reported 6 cases of PE following ophthalmic surgeries.…”
Section: Resultsmentioning
confidence: 99%
“…The posture would allow for the gas to tamponade the retina against the other layers of the globe and the apposition is thought to improve the surgical outcomes [12]. The instructions are often 30-50 minutes for 2 weeks following surgery, but as pointed out by authors, patients often put themselves in that position longer than instructed in hope to improve their outcomes [5]. Weeks of reduced mobility would contribute to the venous stasis arm of the Virchow's triad in the pathogenesis of a VTE.…”
Section: Centralmentioning
confidence: 99%
“…Although VTE among ophthalmic surgical patients is less reported, a growing body of evidence suggests that ophthalmic surgical patients are at an increased risk of VTE ( Kaplan & Reba, 1972 ; Huang & Wei, 2016 ; Brill et al, 2019 ; Law, Chan & Cheng, 2018 ; Wang et al, 2016 ). Studies have shown that VTE is the leading cause of death in patients undergoing ophthalmic surgery ( Kaplan & Reba, 1972 ; Kanbay et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Most ophthalmic surgical patients are middle-aged or older adults ( Lei et al, 2019 ) and are comorbid with other chronic illnesses such as obesity, coronary heart disease, and diabetes ( Liu et al, 2017 ; Gong et al, 2021 ), which are all well-known risk factors for VTE. In addition, most ophthalmic surgeries take more than 30 min and the prolonged immobility in a postoperative prone position after retina surgery also predisposes patients to VTE ( Brill et al, 2019 ). Therefore, VTE prevention for ophthalmic surgical patients deserves closer attention.…”
Section: Introductionmentioning
confidence: 99%
“…According to a survey by the American Society of Retina Specialists in 2018 [ 6 ], 86.9% of retinal surgeons incorporate the FDP in clinical practice. However, maintaining a FDP is arduous, particularly for older and obese people, and may lead to some complications such as pulmonary embolism, ulnar nerve neuropathy, and pressure sore [ 7 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%